ANALYSIS OF UTAUT METHOD TO EXPLAIN SUSTAINABLE INTENTIONS IN USING BUY NOW, PAY LATER SERVICE IN INDONESIA - Muhammad Athaya Dzaky; Albari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The development of financial technology (fintech) has encouraged the emergence of various innovations in digital payment systems, one of which is the Buy Now, Pay Later (BNPL) service. This service allows consumers to make purchases with deferred payments without the need for a credit card, making it a popular alternative in Indonesia. Based on OJK data, the growth of BNPL services will reach 26.59% in April 2025, indicating a significant increase in public adoption of digital payment systems. This study aims to analyze the factors that affect users' sustainable intentions in using BNPL services in Indonesia using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The variables studied included performance expectations, business expectations, social influences, and facility conditions. The results show that ease of use, facility support, and social influence have a stronger effect on users' intention to continue using BNPL services than performance expectations. Therefore, BNPL service providers are advised to focus on improving accessibility, system reliability, and building trust through a community-based approach.